A new cytotype for the El Carrizo deer mouse Peromyscus ochraventer - Irma Urbina Sánchez; María de los Angeles Aguilar Santamaría; Gerardo López-Ortega M (Global Journal of Zoology - Peertechz Publications, 2020)
Peromyscus ochraventer is a rodent species endemic of Mexico. In 1981, Robbins and Baker described its karyotype from one single female which presented 2n = 48 and FN = 60. In this paper we describe the Y chromosome of the male and a new cytotype for the species, 2n=48, FN= 58, that was identified in all of the collected specimens. The FN = 58 is due to one pericentric inversion in chromosome 6, as shown by G-banding pattern.